(untitled) (Global Journal of Management and Business Research, 2014)
Introduction-When investors decide to buy shares or stocks in any company, there is the initial presumption that the company would in turn make profits which would then be delivered to them based on their investment. However, more often than not, there are cases where investors are faced with the situation whereby their investments could go down the drain due to bad corporate governance practices of the company-ies in which the investments are made. Bad corporate governance practices and indeed control fraud have led to insider abuse whereby directors have failed to perform their fiduciary duties in proper management of the companies’ assets.